A Global Governance Approach to FAO: Proximity, Legitimacy & Accountability- Averting the global food crisis - Rocha de Sousa, Miguel (2014)
This paper assesses the different dimensions of Global Governance for International Organizations in different settings and contexts. We focus specifically on the (P,L,A) Proximity, Legitimacy, Accountability approach measuring it by using the Zweifel (2006) framework. We update his approach taking into account the current global crisis since 2008, and construct a new rating and ranking for the Food and Agriculture Organization (F.A.O.). Some policy recommendations, namely for FAO organization are expected, namely trying to avert the global food crisis, and the rating and ranking among other functional organizations such as the IMF, WB, WTO, WFP, and UN. The final goal is to abridge almost all the International Organizations (IO) in the framework of Global Governance and establish a new framework to compare the different working dimensions of appointment, transparency, delegation, deny/over-rule, accountability specifically for F.A.O.